Tinjauan Yuridis Penangkapan Ikan Secara Illegal (Illegal Fishing) Menurut Undang Undang Nomor 45 Tahun 2009 Tentang Perikanan - Warsiman Warsiman; Ervina Sari Sipahutar; Anjani Sipahutar (Mahesa Research Center, 2023)
Indonesia is a country where most of its territory consists of oceans with a population whose development continues to increase and can be expressed in meeting the needs of life, especially in coastal areas, such as fishermen who live in coastal areas generally using a source of life from the marine and fisheries sector. Indonesia as an archipelagic country surrounded by oceans has a strategic position and extraordinary potential with territorial waters, both archipelagic waters and inland waters. In addition, the Indonesian seas also include the sea waters of the Exclusive Economic Zone (EEZ). The economic loss caused by the practice of illegal fishing does not only result in loss of state revenues but also loss of opportunities for catching fish by Indonesian fishermen. If examined more deeply, it can be said that illegal fishing causes a lot of losses, not just counting how many fish have been stolen, but the impact is even wider, the financial burden is borne by the state, such as fuel subsidies (BBM) which are ultimately enjoyed by ships. -illegal vessels, reduced non-tax revenue (PNBP), reduced Indonesian fishermen's job opportunities, because illegal vessels are foreign ships that use their own crew (ABK), catches are generally brought directly abroad (country from ships), threats to the sustainability of fish resources because catches are not detected, both in type, size and quantity.